Six-minute stepper test to assess effort intolerance in interstitial lung diseases - Delourme, J.; Stervinou-Wemeau, L.; Salleron, et al., L. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
The six-minute stepper test (6MST) is a new test for evaluating exercise tolerance. Unlike the sixminute walk test (6MWT) it can be carried out in a limited space. The aim of this study was to compare the 6MST and the 6MWT in patients with various diffuse interstitial lung disease (ILD).6MWT and 6MST were performed the same day in 84 patients with various ILD. The covered distance during 6MWT was compared to the number of steps during the 6MST. We also compared heart rate, oxygen saturation, dyspnoea and leg tiredness on a Borg scale. All the patients successfully completed the tests, and tolerance was considered good. The number of steps completed in the 6MST was strongly correlated with the distance walked in the 6MWT (r²=0.5; p<0.0001). Oxygen desaturation was less frequent and less severe (p<0.0001), heart rate was higher (p<0.0001) and dyspnoea and leg tiredness were more marked (p<0.0001) in the 6MST than in the 6MWT. The 6MST is feasible for patients with ILD. It is a simple, safe, mobile test that is cheap and easy to carry out in all structures.